DETERMINANT OF THE AMOUNT OF RELATED PARTY TRANSACTION: INFLUENCES TAX EXPENSE AND INSTITUTIONAL OWNERSHIP - Monica Melati; Rita Wijayanti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The main purpose of this research is to investigate the impact of related party transactions (RPT) which is related to sales and expenses and institutional ownership on tax expenses. The sampling technique is purposive sampling and the amount of population is 227 consumer goods companies Based on this research population is the listed company of consumer the industry on the Indonesia Stock Exchange with a total sample of 48 and the period of observation years in 2017-2020. This study method uses quantitative methods with a hypothesis test panel data regression analysis tools using IBM SPSS Statistics 26 and the proceeds exhibit that tax expenses of the previous year do not have an influence on the amount related party transactions to sales expense (RPTSE) Related party transactions are comparatively complex on the other side of that, institutional ownership ensures inspections of these transactions then shows institutional variables have an influence on related party transactions related to sales and expense (RPTSE).